MANAJEMEN LABA PADA EVENT PERGANTIAN CHIEF EXECUTIVE OFFICER DI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dhinata, I Putu Surya; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2015)
One of the motivations behind earnings management is management doing the turn of the Chief Executive Officer (CEO). Intersection between the principal and the destination agent and does not produce good performance in office, so it can happen at the indicated earnings management practices when CEO turnover with the pattern of taking a bath. The purpose of this research was conducted to test the earnings management practices at the turn of events CEOs in companies listed in Indonesia Stock Exchange. Purposive sampling method, the company acquired 60 sample and tested with multiple regression analysis techniques and test independent sample t-test was used to test hypotheses based on the value of discretionary accruals (DA) Modified Jones Model. Earnings management practices that lower earnings at the beginning of the new CEO's tenure ditujukkan on research results. The results of the average value of the elements of cost increases greater than the element of the increase in revenue (revenue element = 0.150659 and cost elements = 0.117368).
Keywords: earnings management, chief executive officer